Three-dimensional micro/nanoscale architectures: fabrication and applications. Issue 25 (10th June 2015) - Xu, Quan; Lv, Yunzu; Dong, Chenbo; Sreeprased, Theruvakkattil Sreenivasan; Tian, Ang; Zhang, Hangzhou; Tang, Ying; Yu, Zhiqiang; Li, Neng
Abstract : Novel 3D functional architectures with exquisitely controlled morphology at the micro/nanoscale can be used in various applications including biomedicine, energy and device construction. Abstract : Three-dimensional (3D) functional solids with programmable hierarchical micro/nanoarchitectures are critical for several fundamental applications, including structural composites, microfluidics, photonics, and tissue engineering. Due to the broad range of application possibilities, a large amount of effort has been devoted to the in-depth exploration of various top-down and bottom-up strategies to construct these complex multi-dimensional structures. In this review, we introduce and discuss selected examples of fabrication techniques which have successfully developed large area, novel 3D functional architectures with exquisite control over their morphology at the nano/subnanolevel. Emphasis is placed on the nanofabrication techniques, their salient features as well as advantages. A summary of the emerging application possibilities of such structures, especially in biomedicine, energy, and device construction, is also discussed.